KAJIAN STABILITAS KAPAL SEISMIK PADA KAPAL RISET BARUNA JAYA II - Rizki Adi Nugroho; Arfis Maydino Firmansyah Putra; Dinar Novandia Sunjayani; Tris Handoyo (Oseanika, 2021)
[Study of Ship Stability on Seismic Research Vessels - RV. Baruna Jaya II] Ship safety has become a global issue and the maritime safety commission of the IMO (International Maritime Organization) developed requirements to be accepted by the parties to the International Convention for the Safety of Life at Sea SOLAS 1974 (Safety Of Life At Sea 1974). Meanwhile, ship stability is an important factor in maintaining ship safety from shipwreck by imbalance factor. Through the inclining test and loading on the ship. This study aims to determine the stability of the ship on the KR. Baruna Jaya II as a special research vessel for seismic surveys. The results of the ship stability analysis were then compared with the general criteria for ship stability according to IMO standards and the Indonesian Classification Bureau (BKI). As a result, metacenter height and enforcement value (GZ) met the requirements according to BKI and IMO. Furthermore, in general, all ship stability tests also showed results in accordance with IMO standards. Meanwhile, some conditions that do not meet the requirements can be normalized by fully setting the ballas. Further studies are needed, especially regarding the determination of specifications and placement of fixed ballas for calculating the stability of ships with fixed ballas. Keywords:      Inclining test, ship stability, RV. Baruna Jaya II, IMO, BKI